A LITERATURE REVIEW ON PATHOPHYSIOLOGY AND MODERN APPROACHES TO THE TREATMENT OF NEOVASCULAR EYE DISEASES - Sh.O.Abdullaev; G.N.Mamatkhujaeva; A.K.Abdullaev (Scholar Express Journals, 2022)
Neovascular pathology (NVD) in posterior segment the eye leads to visual deterioration or even loss in several ocular diseases. Proliferative diabetic retinopathy, neovascular age-related macular degeneration, and retinopathy of prematurity are predominant in the list of NVD. Together, these three diseases afflict persons in all stages of life from birth through late adulthood and account for most instances of legal blindness. Thus being aware of the origin, etiology and pathophysiology, clinical manifest and the modern approaches to the management and treatment of these diseases is substantial.
Keywords: Neovascular diseases; growth factor; intravitreal injections